Estimation of S-wave Velocity Structures by Using Microtremor Array Measurements for Subsurface Modeling in Jakarta - Mohamad Ridwan; A. Afnimar; Sri Widiyantoro; Masyhur Irsyam; Hiroaki Yamanaka (Journal of Mathematical and Fundamental Sciences, 2014)
Jakarta  is located on  a  thick sedimentary  layer that  potentially has a very  high  seismic  wave  amplification.  However,  the  available information concerning the  subsurface model and bedrock depth  is insufficient  for a seismic hazard  analysis.  In  this  study,  a  microtremor  array  method  was  applied  to estimate the geometry and S-wave velocity of the sedimentary layer. The spatial autocorrelation  (SPAC)  method  was  applied  to  estimate  the  dispersion  curve, while  the S-wave  velocity  was  estimated  using  a  genetic  algorithm  approach. The  analysis  of  the  1D  and  2D  S-wave  velocity  profiles  shows  that  along  a north-south  line,  the  sedimentary  layer  is  thicker  towards  the  north.  It  has  a positive  correlation  with  a  geological  cross section  derived  from  a borehole down to  a depth of  about 300 m. The SPT data from  the  BMKG site  were used to  verify  the  1D  S-wave  velocity  profile.  They  show  a  good agreement. The microtremor analysis  reached  the engineering bedrock  in a  range from 359  to 608  m  as  depicted by a  cross section  in  the  north-south  direction. The site class was also estimated at each site, based on the average S-wave velocity until 30 m depth. The sites UI to ISTN belong to class  D (medium soil),  while BMKG and ANCL belong to class E (soft soil).